Variable number of tandem repeat polymorphisms of man in Southern Africa. - Marques, Isabel Maria (My University, 1992)
Two classes of hypervariable loci, VNTRs and (CA)n repeats, represent a rich source of highly polymorphic markers in the human genome. The main objective of this study was to assess their usefulness in elucidating the relationships between 17 southern African populations and to assess the feasibility of paternity testing using these hypervariable markers in the local context.
A thesis submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy
Keywords: Polymorphism, Genetic; Africa, Southern; Genetics, Medical